Begalan in Banyumas: The Indigenosm of Islam in the Context of Expressive Obedience of Religion and Culture - Nawawi, Nawawi; Warsito, Chandra; Farhah, Nida Umi; Majid, Nik Suhaida Nik Abdul (Journal of Posthumanism, 2025)
The dialectic of Islam and Javanese culture gave birth to a Sufi attitude that was receptive and adaptive towards Javanese culture. One concrete example of integrating Islamic teachings into local culture is the Begalan tradition in Banyumas, Central Java. Begalan is a traditional ceremony usually held at weddings, where there is a procession of giving provisions or gifts to the groom. The method in this research is qualitative. Begalan culture is a form of expressive obedience where the Banyumas people express the values, advice, and teachings that are important in their lives. This show not only entertains but also educates the public about values that may be rooted in the teachings of the Islamic religion. In this context, the philosophical value of Begalan property teaches people about the purpose of marriage in Islam, namely the formation of a family sakinah, mawaddah, wa rahmah as a form of faith in God Almighty. Expressive observance through this tradition helps strengthen a sense of togetherness and collective identity as a Muslim community that upholds Islamic values. Begalan culture reflects the interaction between Islamic teachings and local Javanese culture, showing how expressive devotion allows adaptation and harmonization between religion and local culture. It illustrates how people can express their observance in a way that suits their cultural context, creating a synergy between religion and local traditions.